La emboscada postpoética de Agustín Fernández Mallo: - Gala, Candelas (Purdue University Press, 2025)
La emboscada postpoética de Agustín Fernández Mallo: física, cognición, contemporaneidad, entropía analyzes the poet’s proposal to rescue, with his Postpoetry, official poetry from its sclerotic stagnation due to its fidelity to worn-out premises, to recover a language connected with matter, and to renew its cognitive value. By means of byways (or drifting) through different disciplines, Postpoetry shares space with television, pop music, videos, the Internet, cinema, the arts, publicity, and the sciences, physics in particular. Postpoetry illuminates the intersection between the tranquility that tradition provides and the disquiet that comes with novelty. There is an ambush because, like Odysseus with the Trojan horse, the postpoet, although he is back from his adventures and much experienced, like the astute Homeric hero, often finds himself being ambushed by the recursiveness of its own tricks; however, he understands that all pronouncements entail their own refutation in the form of irony and parody. Everything rests on the uncertainty of which Werner Heisenberg spoke, or on the yin-yang in the complementarity of that other great quantum physicist, Niels Bohr. We readers are invited to participate in this odyssey where enigmas are never solved conclusively. La emboscada postpoética de Agustín Fernández Mallo: física, cognición, contemporaneidad, entropía analiza la propuesta del poeta de “curar,” con su Postpoesía, a la poética oficial de su estancamiento esclerótico por seguir sujeta a premisas ya desgastadas, recobrar un lenguaje enlazado con la materia y renovar su valor cognitivo. Mediante derivas por diferentes campos del saber, la Postpoesía comparte el espacio con la televisión, la música pop, los vídeos, el internet, el cine, las artes, la publicidad y las ciencias, la física en particular. La Postpoesía busca la intersección entre la tranquilidad que aporta la tradición y la inquietud de lo novedoso. Hay emboscada porque, como Odiseo con el caballo de Troya, el postpoeta está también de vuelta de sus aventuras y como el astuto héroe, se ve a menudo “emboscado” por la recursividad de sus argucias. Pero entiende que toda proclama conlleva su propia refutación en forma de ironía y parodia. Todo queda en la incertidumbre de que habló Werner Heisenberg, o del ying-yang en la complementariedad del otro gran físico cuántico, Niels Bohr. Y a los lectores se nos invita a participar en esta odisea donde los enigmas no se solventan conclusivamente.